Análisis de los créditos del sector microempresarial en la ciudad de Guayaquil, periodo 2014 – 2017 - Jácome García, Lupe Graciela (2019)
This research study studies the factors that affect the granting of loans to the microenterprise sector in the city of Guayaquil during the 2014-2017 period. To be specific, the research work will be carried out in the three main municipal markets of the Ximena parish. which are: Caraguay, South Guasmo and Locks. For the study that was carried out in this research project, topics related to the one being studied were analyzed and it was determined that the work of qualification prior to obtaining the title of Economist of Poaquiza Cornejo, Jenny Tatiana in her subject "The microcredit and its contribution to the economic and social development of the microenterprise sector in the city of Guayaquil in 2015 "is closely related and was very helpful as a guide to emphasize my research work. It was also considered a theoretical analysis added to the Microcredit theory of Herrán Gómez, Javier who defines that "it is a tool of development or is a way of relating in an interactive process to generate human development"……..